Nationalising minority ethnic athletes: Danish media representations of Nadia Nadim around the UEFA women's Euro 2017. Issue 2 (3rd April 2019) - Agergaard, Sine
ABSTRACT: With the rise in nationalism and anti-immigration sentiments in Europe, debate has arisen in several national media when minority ethnic athletes opt to play for the national team of their country of origin. This article aims to examine how minority ethnic athletes who opt to play for the national team in their country of destination express and are ascribed national belonging. To do so, the article draws on Nira Yuval-Davis' distinction between belonging and the politics of belonging as well as perspectives from transnational migration studies. The article is based on a single case study of Danish newspapers' representations of the Danish women's football player of Afghan origin, Nadia Nadim. In the build-up to, duration and aftermath of the UEFA Women's Euro in 2017, Nadim was ascribed Danish identity, while her popularity as a player rose. However, the article points out how athletes who become exemplary others along ethnic and national lines are deprived of their transnational belonging and of their potentially critical voice. Further, the article discusses how ideas of national unity in sport are enacted in the media through apparently innocent descriptions of patriotism and national archetypes seeking to reconcile current divisions in European societies.